A Proposed Ranked-Based Ranking Model on the Impact of International Ranking of Higher Education Institutions on Higher Education Reform in the Kingdom of Saudi Arabia - Ahmed Alduais (Athens Institute for Education and Research, 2020)
To measure the impact of international ranking of higher education institutions on higher education reform in the Kingdom of Saudi Arabia and to propose a ranked-based ranking for the Saudi higher education institutions in addition to a ranking development model. A non-experimental study based on the quantitative data retrieved from five types of rankings (Webometrics, Shanghai, QS, Times Higher Education and Leiden) and qualitative data from the Ministry of Education, in addition to the measure proposed by the researcher (Ranked-based ranking)-are all analysed using descriptive statistics and content analysis. The big gap between the establishment of the Kingdom (1932), the the discovery of the oil (1939) the first established higher education institution (1957), realising the importance of higher education internalization after (2000) and first inclusion of Saudi higher education institution(s) in international rankings (2006)-all indicate a slow progress on educational sector in the Kingdom, especially when compared to the the many pluses the country have. However, the achievements of the Kingdom since the launch of King Abdullah's Education Reform and Development programme have made a minor difference and resulted into having the Kingdom being ranked among the top Arab countries and mong the international higher education rankings. Yet, when comparing this to the new vision 2030-new challenges are rising and this progress seems to be turtling again. What has been achieved so far is a big plus in the history of the Kingdom; what is being intended to be achieved seems to be a shy step and a minor objective; the proposed ranked-based ranking model could be developed towards a comprehensive ranking system; and the proposed model for improving ranking is country specific and might not work for other countries.